Non-synonymous Single Nucleotide Polymorphism on TLR1A gene as a candidate for immune function of Indonesian indigenous chicken - HENI INDRIJANI; NENA HILMIA; ASEP ANANG; MUHAMAD SYAHID PANJI PANGESTU (Society for Indonesian Biodiversity, 2024)
Abstract. Indrijani H, Hilmia N, Anang A, Pangestu MSP. 2024. Non-synonymous Single Nucleotide Polymorphism on TLR1A gene as a candidate for immune function of Indonesian indigenous chicken. Biodiversitas 25: 2434-2441. TLR1A is a candidate gene related to the immune system in chickens, which contributes to disease resilience, which could impact their productivity. This study aimed to determine mutations in the TLR1A gene in three indigenous Indonesian chickens namely, Pelung, Black Kedu and Sentul. A total of 127 DNA samples were used and consisted of 38, 41 and 48 respectively for Pelung, Black Kedu and Sentul chickens. DNA was isolated from white blood cells and amplification of TLR1A gene was conducted in part of exon 4 using PCR with specific primer. The sequencing results for the TLR1A gene were analyzed to identify mutations using the BioEdit and MEGA X programs. The results showed genetic polymorphisms in the TLR1A gene in Indonesian indigenous chicken. One synonymous mutation, g.710C>T, in which amino acid coded leusine at 207th, and four non-synonymous mutation, i.e., g.822A>G, altered amino acids coding from threonine to alanine (T245A), g.835C>T, which altered amino acids coding 249th from threonine to methionine (T249M), g.1015G>A that altered amino acids coding 309th from serine to aspargine (S309N) and g.1165T>G that changed amino acid from arginine to proline R359P. All mutation frequencies for the alleles are lower than those for the non-mutation alleles. The non-synonymous mutation of the TLR1A gene might alter the metabolism of this hormone related to the immune system in chickens.